Validity of fisher effect theory: Evidence from the conventional and Islamic money market in Malaysia - Nurazilah, Zainal; Mohammed Hariri, Bakri; Law, Siong Hook; Syahrir, Zaini; Mohd Faizal, Ab Razak (Romanian Society for Quality Assurance - SRAC, 2021)
This study attempts to examine existence of Fisher Effect theory in Malaysia’s conventional and Islamic money markets. Time series data has been included for the years 2011 to 2018 and consists of two stages of data analysis. First stage analysis examines the existence of a Fisher Effect relationship by applying the Autoregressive Distributed Lag (ARDL) approach as an estimation method. Second stage analysis determines the strength of the Fisher Effect relationship by imposed restriction β=1 using standard asymptotic Chi-square in Wald test. The findings found that the Fisher Effect theory valid in Malaysia’s Islamic money market but there is no evidence for the conventional market. This outcome suggests that the Islamic money market can accurately predict inflation in the future. However, it appears in a weak form of relationship. Overall, outcomes of this study provide benefits for policy-makers since the existence of the Fisher relationship reflects an effective monetary policy for economic growth and sustainable development